Elevated LDL-C, high blood pressure, and low peak V̇O2 associate with platelet mitochondria function in children—The Arkansas Active Kids Study - Diaz, Eva C.; Adams, Sean H.; Weber, Judith L.; Cotter, Matthew; Børsheim, Elisabet (Frontiers in Molecular Biosciences, 2023)
Purpose: To evaluate the association of platelet (PL) mitochondria respiration with markers of cardiovascular health in children ages 7 to 10 years. Methods: PL mitochondrial respiration (n= 91) was assessed by high-resolution respirometry (HRR): Routine (R) respiration, complex (C) I linked respiration (CI), and maximal uncoupled electron transport capacity of CII (CIIE) were measured. The respiratory control ratio (RCR) was calculated as the ratio of maximal oxidative phosphorylation capacity of CI and CI leak respiration (PCI/LCI). Peak V̇O2 (incremental bike test) and body composition (dual-energy X-ray absorptiometry) were measured. Multiple generalized linear regression analysis was used to model the association of measures by HRR with variables of interest: adiposity, low-density lipoprotein (LDL-C) and triglyceride (TG) status (normal vs. elevated) HOMA2-IR, blood pressure status (normal vs. high), and demographics. Results: R and CI-linked respiration positively associated with adiposity, high blood pressure (HBP), and peak V̇O2. R and CI-linked respiration had inverse association with age and elevated LDL-C. CIIE was higher in children with elevated LDL-C (log-β = -0.54, p= 0.010). HBP and peak V̇O2 interacted in relation to RCR (log-β= -0.01, p= 0.028). Specifically, RCR was lowest among children with HBP and low aerobic capacity (i.e., mean peak V̇O2 -1SD). HOMA2-IR did not associate with measures of PL mitochondria respiration. Conclusion: In PL, R and CI-linked mitochondrial respiration directly associate with adiposity, peak V̇O2 and HBP. Elevated LDL-C associates with lower CI-linked respiration which is compensated by increasing CII respiration. PL bioenergetics phenotypes in children associate with whole-body metabolic health status.